PERTANGGUNGJAWABAN PIDANA TERHADAP KORPORASI YANG MELAKUKAN PEMBAKARAN LAHAN MENURUT UNDANG-UNDANG NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP (ANALISIS PUTUSAN PENGADILAN NEGERI BENGKALIS NOMOR 547/PID.SUS/2014/PN.BLS) - Dita Kartika Sari Hasibuan; Alvi Syahrin; Suhaidi Suhaidi; Muhammad Ekaputra (USU LAW JOURNAL, 2019)
ABSTRACT Indonesia is a country with the largest forest area in the world. Indonesia's forest as a source of natural wealth is one of the most basic capitals of national development used to increase Indonesian prosperity. In essence, forest development is, among other things, to be used as plantation land, agriculture and for the prosperity of the people. This was originally expected to be realized but it turns out that it is now just something that seems to be difficult to happen. This is due to the rampant fires or burning of plantation land that continues to occur oday in Indonesia. Land fires/burning is now a very serious problem in Indonesia because it can cause multi-dimensional problems related to economic, social, cultural and environmental aspects. In connection with this, the purpose of this study was: to find out about the provisions of criminal acts of land burning by corporations according to UUPPLH, to find out the criminal liability of corporations that carry out land burning based on UUPPLH, and to determine the analysis of the Bengkalis District Court's decision Number 547 / Pid . Sus / 2014 / PN.Bls. The method used in this study is normative research, with the nature of descriptive analysis, sourced from secondary data with primary legal material, secondary legal material, and tertiary legal material. This research was conducted by collecting data in library studies and document studies analyzed qualitatively using the Statute Approach and Case Approach. The provision of criminal acts of land burning committed by corporations is focused on Law Number 32 Year 2009. The act of environmental crime committed by corporations on land burning is also a material offee of illegal action that causes pollution or environmental damage. The criminal liability of corporations committing land burning based on UUPPLH is the imposition of criminal penalty in accordance with Article 108 jo. Article 116 Paragraph (1) Letter a is a minimum of Rp.3,000,000,000 and a maximum of Rp.10,000,000,000. However, the corporation is subject to a fine of Rp.2,000,000,000 because from the legal facts the corporation in this case is only proven negligent over the quality standards of ambient air in accordance with the provisions of Article 99 Paragraph (1) and additional criminal complements of fire prevention facilities. Based on the analysis of the Bengkalis District Court Number 547 / Pid.Sus / 2014 / PN.Bls. it was found out that the decision of Public Prosecutor's demand and that of the Judge's are not the same. Judge's decision is lighter than the Prosecutor's demand.  The judge verdict was that the defendant was only proven negligent over exceeding the quality standards of ambient air due to land burning. In fact, the land burning committed by the defendant PT. NSP made a huge loss. However, at least the defendant provided the appropriate compensation for the negligence. Here, the thesis writer is in disagreement with the mild judgment of the Panel of Judges because the decision did not provide a deterrent effect on what was done and for the negligence of the defendant, PT. NSP.   Keywords: Criminal Responsibility, Corporations, and Land Burning.